Synthesis and Characterization of a Novel Azo-Dye Schiff Base and Its Metal Ion Complexes Based on 1,2,4-Triazole Derivatives - Nada Ahmed Rasheed Al-qasii; Ali Taleb Bader; Zaied Mosaa (Universitas Gadjah Mada, 2023)
The study focused on producing and examining the properties of the 2-(((3-mercapto-5-(4-nitrophenyl)-4H-1,2,4-triazol-4-yl)imino)methyl)-4-(((4-mercaptophenyl) diazenyl)phenol) ligand (L) and its complexes with three transition metal ions, namely Ni(II), Co(II), and Cu(II). The ligand was formed through diazotization and coupling reactions between 4-aminobenzenethiol and a coupling Schiff base derived from 1,2,4-triazole. The characterization of the ligand and its metal ion complexes was carried out using analytical techniques such as FTIR, 1H- and 13C-NMR, UV-visible spectroscopy, and thermal analysis (TGA and DTG). Various physical methods were employed to synthesize and analyze the properties of the three mononuclear Co(II), Ni(II), and Cu(II) complexes with the azo-dye Schiff's base ligand. Based on the microanalysis and spectroscopic results, it was determined that the coordination between the azo Schiff base ligand and the central metal ion occurred through the NOS-donating atoms of the ligand. The analysis of the electronic spectra revealed that the synthesized Co(II) and Ni(II) complexes exhibited an octahedral geometry, while the Cu(II) complex had a distorted octahedral geometry. The implications of the finding regarding the octahedral and distorted-octahedral geometries include expanding the structural diversity in coordination chemistry, providing insights into ligand-metal interactions, and understanding the influence of geometry on properties.